KONSTRUKSI IDENTITAS GENDER PADA BUDAYA POPULER JEPANG (ANALISIS ETNOGRAFI VIRTUAL FENOMENA FUJOSHI PADA MEDIA SOSIAL) - Latifah Gusri; Ernita Arif; Rahmi Surya Dewi (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study discusses the phenomenon of fujoshi which is a favorite of a woman in enjoying anime and manga that has the genre Yaoi or Boys Love. Yaoi is a genre that tells about same-sex relationships made by men. This research was conducted with qualitative research methods with virtual ethnographic analysis. This study will examine how the construction of gender identity is built on yaoi fans on social media by using the communication theory of gender from Michael Hecht. The results showed that the gender identity of fujoshi was formed through three layers, namely the personal layer, the enactment layer, and the communal layer. This study also found that Fujitsu tends to have multiple identities in their lives. Fujoshi is more willing to show identity about their passion for yaoi on social media.